Pengembangan Konsep Digital Marketing Usaha Mikro Kecil dan Menengah (UMKM) dengan Melalui Sosial Media - Riska Silpiani Saputri; Darius Antoni (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Globalization today is a challenge for Small Medium Enterprises (SMEs) to survive, this Msme's business contributes to spurring economic growth in Indonesia. the dissemination of information is now easier in increasing consumer awareness of the many choices of goods and services that can be selected. currently, there are a lot of SMEs who open their businesses manually without using social media, and there are also SMEs who already use social media but are not too active in using social media. Many SMEs are not too concerned with strategy in opening their business through social media. if SMEs do not use marketing strategies to increase sales, then SMEs will experience a decrease in revenue. for this reason, MSMEs need to look at various potential alternatives to social media to be used as marketing media for SMEs in Palembang city. herefore the need for marketing through digital marketing. The benefits obtained with digital marketing besides being able to reach a wider market and streamline marketing costs, also make marketing space and Time Unlimited. The author uses qualitative research methods with a descriptive approach that is a description of the results of observations and documentation studies. The purpose of this study is to determine the development of the concept of digital marketing of SMEs through social media that will build the interest of SMEs in conducting SMEs development strategies in Palembang city. In conclusion from the results of this study, there are still many SMEs who use marketing techniques without using digital Marketing, therefore it is very necessary to use digital marketing through social media so that it can encourage an increase in the number of sales and expand the coverage area of consumers of SMEs. With this, the author is looking for an SMEs business whose digital marketing development through social media has been successful so that SMEs who have not used digital marketing can understand and learn it in the hope of increasing the income of SMEs.